2010
DOI: 10.1161/strokeaha.110.578245
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Iodinated Radiographic Contrast Material Injection Administration in a Rat Middle Cerebral Artery Occlusion and Reperfusion Model

Abstract: Background and Purpose Observations in human interventional stroke treatment led us to hypothesize that iodinated radiographic contrast material use may contribute to intracerebral hemorrhage. Effects of intra-arterial iodinated radiographic contrast material on hemorrhagic transformation after middle cerebral artery occlusion and reperfusion were studied in a placebo-controlled, blinded preclinical study in rats. Methods Four groups of male Sprague-Dawley rats were studied: saline group (n=8), contrast grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Furthermore, in vitro studies indicate that the type of contrast media applied has an influence on the occurrence and extent of intracerebral hemorrhage. 16 However, our study cannot give further evidence in this regard, because low-osmolar, nonionic contrast was used consistently. Here, additional evaluation is needed.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, in vitro studies indicate that the type of contrast media applied has an influence on the occurrence and extent of intracerebral hemorrhage. 16 However, our study cannot give further evidence in this regard, because low-osmolar, nonionic contrast was used consistently. Here, additional evaluation is needed.…”
Section: Discussionmentioning
confidence: 72%
“…No more than 0.1-0.2 mL is required for adequate evaluation of the microcatheter position within the clot. Careful attention to alteplase infusion within the thrombus is underscored by a study suggesting that microcatheter injection may result in higher rates of hemorrhage, 9 which were not found in this study. A microwire maceration technique was sometimes used in conjunction with RMP.…”
Section: Discussionmentioning
confidence: 50%
“…16,17 A recent study in transient middle cerebral artery occlusion in rats reported that intra-arterial contrast administration, heparin administration, and coadministration of heparin and contrast significantly increased the incidence of cortical hemorrhage compared with control. 18 It should be noted that our retrospective cohort of patients is very different from those enrolled in the IMS trials. In the IMS studies, the median NIHSS score at admission was higher.…”
Section: Macdougall Et Al Iodinated Contrast Media and Cerebral Hemormentioning
confidence: 98%